An observational simulation-based study of the accuracy of intercostal drain placement and factors influencing placement - Tessa Korda; Tammy Baillie-Stanton; Lara Nicole Goldstein (African Journal of Emergency Medicine, 2022)
Introduction: South Africa's significant burden of trauma and respiratory disease requires the regular need for intercostal drain (ICD) insertion. ICD misplacement is associated with significant complications. The aim of this study was to assess ICD insertion site accuracy and the factors affecting accuracy by Emergency Department doctors. Methods: This was a prospective, observational simulation-based study. Prior to participant admission, pertinent thoracic structures were marked on two simulated patients using an invisible marker which could only be seen using ultraviolet light. One by one, study participants were then asked to place a sticker on each side of each patient's chest to indicate where they would insert an ICD. Sticker placements were photographed under ultraviolet light. Placement sites were compared according to the most appropriate and accurate position for insertion (within the area superior to the 6th rib, posterior to pectoralis major and 1cm anterior to the mid-axillary line) as well as the British Thoracic Society's ‘triangle of safety’. Comparisons of accuracy were made between participant rank (junior vs senior doctor), participant experience, simulated patient BMI category and placement side. Results: Insertion site was accurate in 47% of placements and within the ‘triangle of safety’ in 51% of placements. Improved accuracy was associated with greater participant experience (61% vs. 37%, p<0.01), and left-sided chest placement (54% vs 40%, p = 0.02). No difference was found when comparing simulated patient BMI category (low vs high, 43% vs 51%, p=0.18) or participant rank (junior vs senior, 41% vs 51%, p=0.10). Conclusion: Overall accuracy of ICD insertion site was low, and appropriate accuracy was only associated with greater participant experience and left sided placement. Further studies to determine methods to improve ICD placement accuracy are needed.